2021
DOI: 10.1186/s40560-020-00520-w
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of remote-only communication among reference persons of ICU patients during COVID-19 pandemic

Abstract: Background During COVID-19 pandemic, visits have been prohibited in most French ICUs. Psychological effects, for reference persons (RPs), of remote-only communication have been assessed. Methods All RPs of patients referred to ICU for COVID-19 were included. HADS, IES-R, and satisfaction were evaluated at admission, discharge/death, and 3 months. At 3 months, a psychologist provided a qualitative description of RPs’ psychological distress. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 26 publications
0
59
0
Order By: Relevance
“…Restricted family visitation caused by the COVID-19 pandemic increased the incidence of patients' delirium three times from 1.8% to 6.2% [106]. In a restricted visitation situation, most family members experience an extra responsibility and psychological distress [107]. As a result, PICS-F was observed at 22.9% of psychological distress and 2% of PTSD [108].…”
Section: Family Engagement and Online Visitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Restricted family visitation caused by the COVID-19 pandemic increased the incidence of patients' delirium three times from 1.8% to 6.2% [106]. In a restricted visitation situation, most family members experience an extra responsibility and psychological distress [107]. As a result, PICS-F was observed at 22.9% of psychological distress and 2% of PTSD [108].…”
Section: Family Engagement and Online Visitationmentioning
confidence: 99%
“…However, there are several barriers associated with its implementation. The barriers include the inability to communicate owing to patient status (44%), technical difficulties (35%), lack of touch and physical presence (11%), and frequency and clarity of communications with the care team (11%) [107]. However, it is important to note that most families felt that online visitation did not completely replace in-hospital visitation [112].…”
Section: Family Engagement and Online Visitationmentioning
confidence: 99%
“…Psychological distress has clearly increased for patients, family members, and intensive care unit (ICU) staff because of visiting restrictions. [1][2][3][4] Family members of isolated COVID-19 patients in the ICU experience moral injury with prevalence of anxiety and depression of 83% and 73%, respectively. 2 Thus, intensivists are faced with an impossible equation: (i) they should promote interactions between the relatives and the critically ill patients to prevent post-traumatic stress disorder; however, (ii) they need to ensure patient, staff, and visitor safety-and thus respect the restrictions of hospital visits.…”
mentioning
confidence: 99%
“…[1][2][3][4] Family members of isolated COVID-19 patients in the ICU experience moral injury with prevalence of anxiety and depression of 83% and 73%, respectively. 2 Thus, intensivists are faced with an impossible equation: (i) they should promote interactions between the relatives and the critically ill patients to prevent post-traumatic stress disorder; however, (ii) they need to ensure patient, staff, and visitor safety-and thus respect the restrictions of hospital visits. 1 Here, we show a remote-controlled robot that helps to support communication between patients and their relatives.…”
mentioning
confidence: 99%
“…Emerging evidence over the past two decades has shown a clear benefit of family/ essential caregiver presence across patient populations. [4][5][6][7][8] In response to this, a gradual relaxation of visitor restrictions has been seen over the decades. By early 2020, just prior to the COVID-19 pandemic, a review of hospitals by the Canadian Foundation for Healthcare Improvement found that 73% of hospitals had adopted accommodating visitor policies (increased from 32% in 2015).⁹…”
Section: Historical Perspectivementioning
confidence: 99%